The Relationship Between Knowledge, Attitudes, and Supporting Factors Among Women of Reproductive Age Regarding Cervical Cancer and Their Interest in Undergoing an Iva Test in the Service Area of the Talun Community Health Center, Cirebon Regency - Cecep Rohendi; Thysa Thysmelia Affandi; Thysa Shofa Nur Fauzah (CV. Publikasi Indonesia, 2026)
Cervical cancer is the 4th leading cause of death in women worldwide and the 2nd in Indonesia. The prevalence of cervical cancer in 2022 in Asia was 1,186,812 cases, Indonesia 36,964 cases, West Java 565 cases. Early detection of cervical cancer can be done using the IVA test method. There are several factors for WUS in conducting the IVA test, including knowledge, attitude, supporting factors and interest. This research aimed to To determine the correlation between knowledge, attitudes and supporting factors of women in reproductive age regarding cervical cancer with interest in conducting IVA tests in the working area of Talun Health Center, Cirebon Regency. This research used an analytic observational design to 100 women of reproductive age in the working area of Talun Health Center using a cross-sectional approach with a questionnaire. Data analysis used the Spearman correlation test (bivariate) and logistic regression test (multivariate). The result bivariate analysis showed a significant correlation between women of reproductive age's knowledge (P<0.05), attitude (P<0.05), and supporting factors based on affordability (P<0.05), information sources (P<0.05), and accessibility of health facilities (P<0.05) with interest to commit IVA test. Multivariate analysis showed attitude sources were the most influential factor on the interest in conducting the IVA test (P<0.05). Attitude is the most significant factor correlated with the willingness of women of reproductive age in the Talun Community Health Center working area to undergo IVA tests. Therefore, healthcare providers should enhance educational efforts and understanding regarding cervical cancer and the IVA test.